Technostress, anxiety, and coping strategies in online teaching among nurse educators - Banaticla, Melania S.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
The use of technology in educational processes accompanies adaptation issues due to the rapid development and cost of technology, internet connectivity, need for electricity, suitable space at home and sufficient knowledge in navigating online platforms (Munoz, et. al., 2020). The goal of this study is to determine the technostress, anxiety, and coping strategies in online teaching of nurse educators in universities and colleges of nursing in Laguna. Further, the study probed the relationship between respondents’ level of technostress and level of anxiety, level of technostress and coping strategies, and level of anxiety and coping strategies. The findings revealed that the level of technostress among nurse educators in Laguna was low, have a mild level of anxiety, and very high in utilizing coping strategies. There was a significant relationship between the respondents’ level of technostress and level of anxiety, as the probability values of 0.006 (learning-teaching and profession oriented), 0.039 (technical oriented), 0.008 (personal-oriented), and 0.001 (social-oriented) were less than the 0.01 and 0.05 significance level respectively, thus implied that the lower the respondents’ level of technostress the more the respondents’ have mild anxiety, there was no significant relationship between the respondents’ level of technostress and coping strategies, as the probability values 0.586 (learning-teaching process oriented), 0.211 (profession oriented), 0.960 (technical oriented), 0.506 (personal oriented), and 0.297 (social oriented) are more than 0.05 significance level, this implied that the hypothesis that there is no significant relationship between the respondent’s level of technostress and coping strategies was accepted, and lastly, there was no significant relationship between the respondents’ level of anxiety and coping strategies, as the probability value 0.192 is more than 0.05 significance level, therefore, the hypothesis that there is no significant relationship between the respondent’s level of anxiety and coping strategies was accepted.